ANALISIS KADAR VITAMIN D PADA PENERIMA VAKSIN SINOVAC SEBAGAI GAMBARAN SISTEM IMUNITAS - Siti Nur Husnul Yusmiati; Aprilia Aly Damayanti; Christina Destri Wiwis Wijayanti; Tonny Watoyani (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2023)
The body's immune system is a system that detects a wide variety of outside biological influences, organisms will protect the body from infections, bacteria, viruses to parasites. During the current pandemic, the immune system is very important to prevent exposure to COVID-19. Efforts are made to be able to sufficient intake of vitamins and vaccinations. Vitamin D is one that is needed to prevent exposure to viruses. This study aims to determine vitamin D levels in sinovac vaccine recipients as an illustration of the immune system. This scientific paper research uses primary data analytic observation method with a cross-sectional design supported by literature studies, namely by describing the results of the research in the form of a percentage (%) decrease and increase in vitamin D compared to normal values. The results of the research on vitamin D levels receiving the Sinovac vaccine found that 92% or 23 patients out of 25 patients showed vitamin D levels were still within normal values and 8% or 2 patients showed vitamin D levels below normal values. It can be concluded that some of the research samples were in the normal range so that the immune system as the response of vitamin D to vaccines is still being seen. Keywords : SINOVAC Vaccine, Vitamin D, Immune System.